2017
DOI: 10.4269/ajtmh.17-0533
|View full text |Cite
|
Sign up to set email alerts
|

The Multifactorial Epidemiology of Blackwater Fever

Abstract: Blackwater fever is a massive hemolytic event usually occurring in the context of repeated falciparum malaria infections and intermittent quinine use. Its etiology is poorly understood, and it is rarely seen today. Historical epidemiological observations from the 20th century demonstrated variable patterns in prisoners in Andaman Islands, refugees in Macedonia, canal workers in Panama, expatriates in Rhodesia, and Second World War soldiers. Rates of blackwater fever per 1,000 malaria cases varied over two orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Also, certain viral and bacterial diseases have been linked to the occurrence of BWF [9, 10]. Its pathophysiology thus remains unclear [1, 9, 10]. In the present study, we report on four blackwater fever cases in adults treated with quinine for severe malaria.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Also, certain viral and bacterial diseases have been linked to the occurrence of BWF [9, 10]. Its pathophysiology thus remains unclear [1, 9, 10]. In the present study, we report on four blackwater fever cases in adults treated with quinine for severe malaria.…”
Section: Introductionmentioning
confidence: 84%
“…BWF is found in areas where malaria is endemic [1, 11]. Several authors have reported on its recrudescence, especially in Africa [9, 12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations